2004
DOI: 10.1111/j.1439-0418.2004.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological traits and life table of the exotic Harmonia axyridis compared with Hippodamia variegata, and Adalia bipunctata (Col., Coccinellidae)

Abstract: As part of an environmental risk assessment study of exotic natural enemies used in inundative biological control, life-history characteristics of Harmonia axyridis (Pallas), Hippodamia variegata (Goeze) and Adalia bipunctata (L.) (Col., Coccinellidae) were quantified under laboratory conditions at 25°C on Myzus persicae (Sulzer) as prey. Comparative studies showed significant differences among pre-adult development times: H. axyridis developed slower ( X ¼ 19.8 days) than H. variegata ( X ¼ 18.1 days) and A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
118
9
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 34 publications
13
118
9
7
Order By: Relevance
“…Reduced consumption of some aphids has been ascribed to certain alkaloids and other allelochemicals not suitable for the constitution and metabolism of the ladybeetles (Okamoto 1966 (ElHag and Zaitoon 1996), and 9.4 days for H. variegata reared on Myzus persicae (Lanzoni et al 2004). Variation in the presented findings may be ascribed to factors such as prey species, host plant of prey, rearing conditions, etc., that are reported to affect various biological parameters (Lanzoni et al 2004). Besides, geographical variations in the predator-prey system may also be important (Dobzhansky 1933).…”
Section: Pre-adult Development and Survivalmentioning
confidence: 76%
See 4 more Smart Citations
“…Reduced consumption of some aphids has been ascribed to certain alkaloids and other allelochemicals not suitable for the constitution and metabolism of the ladybeetles (Okamoto 1966 (ElHag and Zaitoon 1996), and 9.4 days for H. variegata reared on Myzus persicae (Lanzoni et al 2004). Variation in the presented findings may be ascribed to factors such as prey species, host plant of prey, rearing conditions, etc., that are reported to affect various biological parameters (Lanzoni et al 2004). Besides, geographical variations in the predator-prey system may also be important (Dobzhansky 1933).…”
Section: Pre-adult Development and Survivalmentioning
confidence: 76%
“…The 4 th instar larvae suffered more as the prey abundance decreased, as the higher metabolic needs could not be catered to (Cividanes et al 2010). Larval survival in the range of 50-75% has been reported for H. variegata by different studies (ElHag and Zaitoon 1996; Lanzoni et al 2004;Wu et al 2010). Wu et al (2010) reported the adult emergence of H. variegata fed A. gossypii, reared on five host plants, varied from 87.23 to 100%.…”
Section: Pre-adult Development and Survivalmentioning
confidence: 99%
See 3 more Smart Citations